Pembelajaran Berbantuan Aplikasi Graspable Math pada Materi SPLDV untuk Melatih Pemahaman Matematis Siswa - Taofik, Agna Ilma; Priatna, Nanang (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2022)
This study aims to describe the use of Graspable Math learning media in the material of the Two-Variable Linear Equation System (SPLDV) to train mathematical understanding skills. This study was conducted on 8th-grade students with as many as six people as subjects using a qualitative methodology. The instruments used were math comprehension test sheets and interview guidelines. The results of this study show that the Graspable Math application can be used as a practical medium for students' mathematics learning. This implies that the use of the Graspable Math application on SPLDV material at the junior high school level can help students' understanding of mathematics, especially in algebraic material which includes operations and substitution between tribes